Memudarnya Budaya Dayung pada Suku Biak Kafdarun: Analisis Faktor Internal & Eksternal - Wattimena, Jonadab (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze the internal and external factors that lead to the waning preservation of paddle culture in the Biak Kafdarun Tribe in Raja Ampat. Paddle culture, which is an important traditional heritage, faces challenges due to modernization, globalization, and lack of government attention. The method used is descriptive qualitative with a constructivistic paradigm, utilizing in-depth interviews, participatory observation, and literature study as data collection techniques. The results showed that internal factors include the low response of the younger generation to cultural preservation, decreased community concern, and a cultural identity crisis due to the influx of outside culture. External factors include modernization, lack of government support, and lack of socialization about the importance of culture as a community identity. The research conclusions emphasize the need for a holistic approach to cultural preservation, including strengthening community awareness, active government involvement, and adaptation of traditions to the modern context to maintain the relevance of rowing culture in people's lives. The findings provide a basis for the development of more inclusive and sustainable cultural preservation policies and programs.